Detection of antibodies against Aujeszky´s disease virus in low level management pig farms in Lima, Peru - Castillo E., Ana (2016)
The aim of this study was to detect antibodies against the virus of Aujeszky’s disease (ADV) in low level management pig farms in Lima, Peru. Blood samples were collected (n=463) from apparently healthy pigs, regardless of sex and mostly between 130 to 150 days old. The animals were from 13 districts of Metropolitan Lima. Neutralizing antibodies against ADV were analysed by the virus neutralization test. All samples resulted negative to antibodies against ADV.